2022
DOI: 10.29333/ejmste/12425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CLIL combined with language instruction on language learning and the role of individual and institutional factors in students’ perspectives: Empirical evidence from Kazakhstan

Abstract: Content and language integrated learning (CLIL) is still a growing area of research. In this study, we investigated the effect of a one-semester CLIL intervention combined with English language instruction on university students' general English skills the associations between institutional and individual factors and views on CLIL. A total of 105 students from two academic programs (biology-chemistry, and physic-informatics) at a private university in Kazakhstan participated in the study. Quantitative data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Interestingly, EMI research in Kazakhstani downplays professors' linguistic adaptation as "pedagogical habitus engagement" and how their "embodied cognitive and corporeal habitus" increases or devalues their capitals (Fataar & Feldman, 2017, p. 188); they merely point to the factors that influence EMI teaching and the effectiveness of approaches and methods in language education and pedagogy. For example, Goodman et al (2022) found structural, pedagogical, sociolinguistic, and cultural factors that need to be considered when implementing EMI interventions, while Satayev et al (2022) emphasised the crucial role of content and languageintegrated learning (CLIL). Polatova et al ( 2020) investigated the effectiveness of digital tools and mobile applications in improving students' communicative competence in business English courses.…”
Section: Taking Stock Of the Kazakhstani Higher Education (He) Fieldmentioning
confidence: 99%
“…Interestingly, EMI research in Kazakhstani downplays professors' linguistic adaptation as "pedagogical habitus engagement" and how their "embodied cognitive and corporeal habitus" increases or devalues their capitals (Fataar & Feldman, 2017, p. 188); they merely point to the factors that influence EMI teaching and the effectiveness of approaches and methods in language education and pedagogy. For example, Goodman et al (2022) found structural, pedagogical, sociolinguistic, and cultural factors that need to be considered when implementing EMI interventions, while Satayev et al (2022) emphasised the crucial role of content and languageintegrated learning (CLIL). Polatova et al ( 2020) investigated the effectiveness of digital tools and mobile applications in improving students' communicative competence in business English courses.…”
Section: Taking Stock Of the Kazakhstani Higher Education (He) Fieldmentioning
confidence: 99%
“…Originally, CLIL was frequently linked to very general language learning aims and glossed as an endeavour to make English more accessible to learners in mainstream education [12]. CLIL has a great potential for the language development that is claimed to be a necessary condition for success and content learning in English medium education [13].…”
Section: сравнительный анализ уровней владения английским языком сред...mentioning
confidence: 99%